More Than Just Wait Time? Regional Differences in Liver Transplant Outcomes for Hepatocellular Carcinoma. Issue 4 (April 2019) - Hogen, Rachel; Lo, Mary; DiNorcia, Joseph; Ji, Lingyun; Genyk, Yuri; Sher, Linda; Dhanireddy, Kiran
Abstract : Background: Regional allocation of deceased donor livers has led to variable wait times for hepatocellular carcinoma (HCC) patients on the liver transplant list. The purpose of our study was to evaluate how regional differences in wait time affect outcomes for HCC patients. Methods: A retrospective, observational study was performed using the Organ Procurement and Transplantation Network database from February 27, 2002, to September 25, 2015. The cumulative incidences of transplant and waitlist death as well as intention-to-treat and posttransplant survival were evaluated for patients 18 years or older listed for deceased donor liver transplantation with stage II HCC exception points in each United Network for Organ Sharing region. A multivariable analysis of predictive factors for posttransplant survival was performed. Results: Cumulative incidence of transplant decreased and cumulative incidence of waitlist death increased as regional wait time increased. Intention-to-treat survival decreased with increased regional wait time with long wait time regions 1, 5, and 9 having significantly lower intention-to-treat survival compared with many of the shorter wait time regions ( P < 0.05). Wait time did not predict posttransplant survival. Significant predictive factors of posttransplant survival included alpha-fetoprotein, size of the largest tumor, number of tumors, age of the recipient, laboratory model for end-stage liver disease, donor risk index, period of transplantation, and region ( P < 0.05). Conclusions: Wait time inequality affects waitlist mortality and intention-to-treat survival but does not affect posttransplant survival. Posttransplant survival is predicted by tumor biology, graft quality, recipient age, underlying liver function, and region. Regional environments of HCC care seem to drive posttransplant survival.